Financial development, energy consumption, technology, urbanization, economic output and carbon emissions nexus in BRICS countries: an empirical analysis. Issue 2 (28th October 2020) - Raghutla, Chandrashekar; Chittedi, Krishna Reddy
Abstract : Purpose: The study investigates the impact of financial development, urban population, technology and energy consumption on economic output and carbon emissions in Brazil, Russia, India, China and South Africa (BRICS) economies. Design/methodology/approach: The study uses Johansen Fisher type panel cointegration, fully modified ordinary least square and heterogeneous panel causality tests to examine long-run, long-run elasticities and short-run relationships. For conducting the tests, the study selected five emerging economies, i.e. Brazil, Russia, India, China and South Africa and used balanced panel data for the period between 1998 and 2016. Findings: The empirical results confirm the presence of a long-run cointegration relationship among the variables. We find that financial development, technology and energy consumption have a considerable positive impact on economic output. Also, financial development, urban population and technology help reduce carbon (CO2) emissions and ensure an improved environmental quality in the long run in the five emerging economies. In the short run, a bidirectional causal relationship is noticed between financial development and CO2 emissions. Practical implications: Clean energy, technological development and investments by public–private partnerships are required in the public and private sectors to reduce carbon emissions. This not only ensures improved environmental quality but also increases energy efficiency, thereby reducing dependency on traditional energy consumption. Originality/value: As its contribution to the extant literature, the study examines the impact of financial development, energy consumption, technology, urbanization, economic output and carbon emissions in BRICS economies. The findings of the research suggest both the governments and policymakers of these five emerging economies to develop more effective policies toward bolstering the financial development and increasing the use of technology. These, in turn, ensure sustainable development with low CO2 emission in the future and, eventually, pushing those five emerging market economies toward sustainable economic growth.